Struktur Sel Epidermis Dan Stomata Aegiceras corniculatum D dan Rhizophora apiculata pada Muara Sungai Desa Poka dan Desa Leahari - Sabandar, Agave; Hiariej, A.; Sahertian, D. E. (INSTITUT AGAMA ISLAM NEGERI AMBON, 2021)
Research has been carried out to determine the cell structure of the epidermis and stomata in some mangrove plants in the species Aegiceras corniculatum and Rhizophora apiculata. Descriptive method is used to describe the cell structure of the epidermis and stomata of Aegiceras corniculatum and Rhizophora apiculata and quantitative leaves to calculate the number of stomata, number of epidermis and stomata index based on nail polish on the cross section of epidermal cells on the lower underside of the leaf using a light microscope, while the incision longitudinal to determine leaf thickness between the upper epidermis and the lower epidermis. The results showed that the two mangrove species that grow in the mouth of the Poka and Leahari villages namely Aegiceras corniculatum and Rhizophora apiculata were found to have the same anatomical structure and leaf anatomical characteristics in terms of the shape of epidermal cells, rectangular, octagonal, elongated, and irregular. Aegiceras corniculatum and Rhizophora apiculata have anomositic stomata type because neighboring cells surround the stomata and have the same shape as epidermal cells. Mangrove species in the river estuary of Poka Village have higher number of stomata and smaller epidermal size and lower stomata index than mangrove species in Leahari Village due to the influence of the shade. Keywords: Aegiceras corniculatum, Rhizophora apiculata, Epidermal cells,